PENGARUH FRAUD DIAMOND, CORPORATE GOVERNANCE, DAN KOMPLEKSITAS BANK TERHADAP FINANCIAL STATEMENT FRAUD PADA PERUSAHAAN PERBANKAN - Centhya Wati; Windhy Puspitasari (Jurnal Akuntansi Trisakti, 2017)
This research aimed to examine the effect of diamond fraud, corporate governance and complexity of the bank to financial statement fraud in companies engaged in banking activities using secondary data. The population in this research was banking companies that listed in Indonesia Stock Exchange for the period 2013-2015. The method used is multiple regression analysis by purposive sampling as sampling method. Selected samples of 30 companies during of 3 periods are 90 samples. Data were obtained through the annual financial statements which have been provided in the Indonesia Stock Exchange. The results showed that pressure has significant positive effect on financial statement fraud, while opportunity, rationalization, capability, corporate governance and complexity have not significant effect on financial statement fraud. Adjusted R Square value of 0,115 can illustrate that the dependent variable was explained by the independent variable variabelitas for 11,5% while 88,5% are influenced by the other variables